Writing apprehension: an unnoticed page from the book of anxiety - Witiw, Taylor (My University, 2014)
This paper ties together some of the limited research done on writing anxiety or writing apprehension. It considers the scope of this anxiety, treatment options, and illustrates the importance of intervention. Lastly, it calls for further research and attention for writing anxiety.
Keywords: writing anxiety; writing apprehension